PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Nelsi Anggraini; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of capital structure on financial performance on a pharmaceutical company listed on the Indonesia Stock Exchange period 2010-2014. The capital structure is used as the independent variable (X) is the indicator Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), and Longterm Debt To Equity Ratio (LDER). Whereas the that is used as the dependent variable (Y) is a financial performance Return on Assets (ROA).This study uses secondary data, annual financial statements pharmaceutical company listed on the Indonesia Stock Exchange period 2010-2014. Sampling was done by purposive sampling the sample used is 8 pharmaceutical companies. The analysis technique used is a simple linear regression, multiple linear regression, coefficient determination test, t test, and test f. Data was analyzed by linear regression analysis using software SPSS 21.The results showed that the variables DAR partially (t test) significantly affects the ROA, whereas the DER and LDER no significant effect on ROA. The results of simultaneous (f test) showed a significant influence of capital structure DAR, DER, LDER together on the financial performance ROA.Keywords : Capital Structure (DAR, DER, LDER), the performance of Treasury (ROA)